2011
DOI: 10.1105/tpc.110.081919
|View full text |Cite
|
Sign up to set email alerts
|

ETOILERegulates Developmental Patterning in the Filamentous Brown AlgaEctocarpus siliculosus 

Abstract: Brown algae are multicellular marine organisms evolutionarily distant from both metazoans and land plants. The molecular or cellular mechanisms that govern the developmental patterning in brown algae are poorly characterized. Here, we report the first morphogenetic mutant, e´toile (etl), produced in the brown algal model Ectocarpus siliculosus. Genetic, cellular, and morphometric analyses showed that a single recessive locus, ETL, regulates cell differentiation: etl cells display thickening of the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…Ectocarpus therefore appears to be a relevant model to explore the emergence of complex multicellularity in the brown algae. For the present, however, Ectocarpus developmental biology is in its infancy and, although several interesting developmental mutants have been described Le Bail et al 2011;Peters et al 2008), it will probably be some time before the molecular mechanisms underlying multicellular development are described and experimentally validated in any detail in this species.…”
Section: Brown Algal Developmental Complexitymentioning
confidence: 98%
See 1 more Smart Citation
“…Ectocarpus therefore appears to be a relevant model to explore the emergence of complex multicellularity in the brown algae. For the present, however, Ectocarpus developmental biology is in its infancy and, although several interesting developmental mutants have been described Le Bail et al 2011;Peters et al 2008), it will probably be some time before the molecular mechanisms underlying multicellular development are described and experimentally validated in any detail in this species.…”
Section: Brown Algal Developmental Complexitymentioning
confidence: 98%
“…Finally, a morphogenetic mutant, étoile (etl), has also been described (Le Bail et al 2011). This mutation effects both cellular differentiation and growth habit (branching).…”
Section: Experimental Investigation Of the Molecular Mechanisms Undermentioning
confidence: 99%
“…The latter transport photosynthate in a manner analogous to the land plant vascular system (Buggeln 1983). For the present, however, Ectocarpus developmental biology is in its infancy and, although several interesting developmental mutants have been described Le Bail et al 2011;, it will probably be some time before the molecular mechanisms underlying multicellular development are described and experimentally validated in any detail in this species. Progress in this domain has been hampered by the absence of a model system adapted for the dissection of developmental pathways.…”
Section: Brown Algal Developmental Complexitymentioning
confidence: 99%
“…The variability in the pattern of early development in Ectocarpus contrasts with the highly ordered development of other model organisms such as Fucus or Arabidopsis. A recent study has shown that a mutation at the ETOILE locus results in a modified pattern of early development, mutant algae initiating branching more rapidly than wild-type individuals (Le Bail et al 2011). …”
Section: Morphogenesismentioning
confidence: 99%